Urban School Success: Lessons From a High-Achieving Urban School, and Students' Reactions to Ferguson, Missouri. Issue 8 (November 2019) - Wiggan, Greg; Watson-Vandiver, Marcia J.
Due to the recent racially motivated killings in Ferguson, Missouri (2014); Staten Island, New York (2014); Cleveland, Ohio (2014); Charleston, South Carolina (2015); Baton Rouge, Louisiana (2016); and Dallas, Texas (2016), racial and ethnic tensions have heightened across the United States. Whereas schools would seem like optimal spaces for racial inquiry and promoting understanding, most classroom lessons have been standardized to avoid critical race discussions. Thus, the transformative power of education is restricted when conversations about real issues in society are avoided. This qualitative case study examines Fannie Lou Hamer Academy (FLHA)—pseudonym, a high-performing urban school that utilizes critical antiracism education. The findings suggest that multicultural curriculum helps students develop "self-knowledge, " meaning a personal awareness of their race and identity. Participants describe how self-knowledge provides corrective history, a response to negative media portrayals of minorities, and helps students understand current events such as the racial unrest in Ferguson, Missouri. The implications of these findings reveal the central role of the curriculum in shaping positive student identities and helping to mediate social conflicts.